ZnO nanobelt based conductometric H2and NO2gas sensors - A. Z. Sadek (2018)
Conductometric H2and NO2gas sensors based on single-crystalline ZnO nanobelt sensitive layers have been developed. These layers were deposited using a rf magnetron sputterer. TEM and SEM characterization methods were employed to study the morphology of the nanobelts. These sensors were exposed to H2and NO2gases at operating temperatures between 225°C and 420°C. Study showed that sensors responded with highest magnitude at above 300°C. The fastest response and recovery times, with greater repeatability occurred at 385°C and 350°C for H2and NO2gases, respectively. Sensor with ZnO nanobelts has a much lower optimum operational temperature than that of conductometric sensors with other forms of ZnO crystal layers. © 2005 IEEE.